Animal traction in Nigeria - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
An important feature of agriculture in the subhumid zone is the presence of seasonally inundated low-lying valleys or fadamas. These may be only one or two metres lower than the surrounding areas but they differ markedly in their agricultural...